Developing integrated solid waste management framework and strategies for Malaysian Higher Education Institutions / Kam Hui Wen - Kam , Hui Wen (2017)
Changing consumption patterns and increasing demand for material resources in business has made solid waste management (SWM) more challenging than ever, particularly in developing countries. Most research into SWM and recycling initiatives mostly discussed in developed countries and municipalities instead of institutional level of operations. One institutional business in particular, the higher educational sector, poses distinct roles and stewardship principles in the natural world. Evidence suggests that strategic planning could considerably improve the effectiveness of SWM. However, existing SWM practices among Malaysian institutions remain in their infancy, and the country still suffers from heavily reliance on landfills. There is a lack of current research exploring the current state of institutional SWM initiatives and strategic impacts which may hamper sustainability business practise and stewardship. For that reason, this research aimed to identify the key success factors, and empirically assesses the relationship between strategic implications; i.e. legislation, environment, economic and social aspect between the institutions. A mixed-method research design via sequential approach was adopted for data collection and analysis. This research commenced with a robust literature review presenting a theoretical framework that embraces strategic performance measurement on institutional SWM. The theoretical framework focuses on seventeen (17) SWM factors with five (5) strategic implication variables has effect to sustainable FM practices. Expert interviews with 10 interviewees responsible in managing their institutional operations were piloted to validate the variables under study. Through expert interviews, fourteen (14) SWM factors were shortlisted and five (5) strategic implication variables were validated. A macro level questionnaire survey was then employed with 129 questionnaires returned. The survey instrument analyses the cause-effect relationship between SWM factors and strategic implication variables. Correlation analysis revealed a relationship between the principal SWM factors implemented between institutions with the strategic impacts. Hierarchical multiple linear regression analysis was performed to further examine the differences between the principal SWM factors which had an effect on the strategic implication variables. As the result, five regression models for each strategic implication variable were established. These findings confirmed that SWM factors for Malaysian higher education institutions were significantly correlated to strategic implications. A strategic institutional SWM performance framework was developed based on the regression models produced, which can be employed as a decision-making tool. Findings this research highlights innovative solutions for facilities managers and managers at board-level in terms of practical SWM advice, as well as describing how such initiatives may encourage sustainable business practices.